Effects of sport participation on adolescent self-esteem and body-image: differences in gender and types of sports explored - Birgir Páll Ómarsson 1989- (2013)
Sport participation has been shown to positively influence self-esteem and body-image of adolescent youth. This effect was measured in a sample of Icelandic participants, with the effects of gender and participation in individual and team sports explored. The study used previously gathered data “Ungt Fólk á Íslandi 2010” (Youth in Iceland) collected by The Icelandic Centre for Social Research in the fall of 2010. The study was implemented on a sample of 1994 participants from the previously gathered data. The Rosenberg scale of self-esteem was used to measure participants’ self-esteem and the Offer scale of body-image to measure participants’ body-image. Participants´ weekly sport participation and type of sports they practiced, individual or team-sports, were also measured. The results show that participants who practice sports on a weekly basis have significantly higher self-esteem and body-image than participants who do not. Participants who practice individual sports have significantly higher self-esteem than participants in team-sports. Male participants had significantly higher body-image than female participants. Keywords: sport participation, self-esteem, body-image, individual-sports, team-sports Sýnt hefur verið fram á jákvæð áhrif íþróttaiðkunar á sjálfsálit og líkamsímynd. Áhrif íþróttaiðkunar á sjálfsálit og líkamsímynd ungmenna var rannsökuð, þar á meðal áhrif kyns og einstaklings- og hópíþrótta á sjálfsálit og líkamsímynd. Rannsóknin var byggð á gögnum frá Rannsóknum og greiningu sem safnað var haustið 2010. Rannsóknin var framkvæmd á úrtaki sem samanstóð af 1994 þátttakendum. Til að mæla sjálfsálit þátttakenda var Rosenberg scale of self-esteem notaður og til að mæla líkamsímynd var Offer scale og body-image notaður. Einnig var vikuleg þátttaka í íþróttum, tegund íþrótta stundað og kyn þátttakenda mæld. Niðurstöður sýndu að þátttakendur sem stunduðu íþróttir vikulega mældust með markækt hærra sjálfsálit og líkamsímynd en þeir sem gerðu það ekki, einnig mældust þátttkendur sem stunduðu ...